Systematic review of treatment strategy for recurrent hepatocellular carcinoma: Salvage liver transplantation or curative locoregional therapy. Issue 8 (February 2019) - Wang, Hong-Liang; Mo, Dun-Chang; Zhong, Jian-Hong; Ma, Liang; Wu, Fei-Xiang; Xiang, Bang-De; Li, Le-Qun
Abstract: Aims: The aim of our systematic review was to compare the efficacy of salvage liver transplantation (SLT) versus curative locoregional therapy (CLRT) for patients with recurrent hepatocellular carcinoma (HCC). Methods: Studies comparing the SLT with CLRT for patients with recurrent HCC were selected from database of PubMed, EMBASE, and Cochrane library. The outcomes including overall survival, disease-free survival, and complications were abstracted. Individual and pooled odds ratio (OR) with 95% confidence interval of each outcome was analyzed. Results: Seven retrospective studies involving 840 patients were included. There is no difference between SLT and CLRT group regarding the1- and 3-year overall survival rates. However, the 5-year overall survival and 1-, 3-, 5-year disease-free survival were significantly higher after SLT than after CLRT (OR = 1.62, 95% CI 1.09–2.39, P  = .02; OR = 4.08, 95% CI 1.95–8.54, P  = .0002; OR = 3.63, 95% CI 2.21–5.95, P  <.00001; OR = 5.71, 95% CI 2.63–12.42, P  <.0001, respectively). But CLRT was associated with fewer complications and shorter hospital-stay compared with SLT. For SLT compared with repeat hepatectomy (RH), the subgroup analysis indicated that SLT group had a significantly higher 3- and 5-years disease-free survival than the RH group (OR = 3.23, 95% CI 1.45–7.20, P  = .004; OR = 4.79, 95% CI 1.88–12.25, P  = .001, respectively). Conclusion: The efficacy of SLT may be superior to that of CLRT in the treatment of recurrent HCC. However, considering the similar overall survival rate and current situation of donor shortage, RH is still an important option for recurrence HCC.